Polonistyczne implikacje doboru i układu treści w podręcznikach literatury dla uczniów szkół średnich Galicji i Królestwa w latach 1867-1918 = Polish studies implications of selection and arrangement of contents in school-books for pupils of secondary schols in Galicia and the Congress Kingdom of Poland in years 1967-1918 - Marchewa, Janusz (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Presented essey is a starting-point for more comprehensive cycle of studies on the structure and function of school-book in teaching of literature. The main aim was the maintenance of evolutional course of literature school-books by the presentation, among other things, teaching achievement in this field, as the real value of school-book is being revealed only from retrospective view. Therefore it is so important in order to expressing the directions at the authors of school-books not to reveal the truth, which is well-known, but refer to it creatively.
Keywords: literatura; nauczanie; Galicja; Królestwo Polskie; 19-20 w.